Pengaruh Kredibilitas Influencer Dianty Annisa Dan Daya Tarik Konten Media Sosial Terhadap Keputusan Pembelian Produk Saudaree Melalui Platform Shopee - Ariska Mananti; Nazwa Rahila Fauzhiansyah; Dea Maharani Siahaan; Intan Rizki Ramadani; Ririn Jarima Putri; Derizka Inva Jaswita (Jurnal Intelek Insan Cendikia, 2026)
Abstract   This study aims to determine the influence of influencer credibility (Dianty Annisa) and social media content attractiveness on purchase decisions for Saudare products through the Shopee platform. The background of this research is driven by the rapid development of social media, which is extensively used as a promotional tool by businesses. Influencer credibility is considered capable of building consumer trust, while attractive social media content can increase consumer interest and the urge to make a purchase. This study utilizes a quantitative method with a descriptive approach. Research data were obtained by distributing questionnaires to consumers who had viewed Saudare product promotions through Dianty Annisa’s social media accounts and subsequently made purchases on Shopee. Data analysis techniques include validity tests, reliability tests, multiple linear regression analysis, as well as t-tests and F-tests to determine the partial and simultaneous effects of influencer credibility (X1) and social media content attractiveness (X2) on purchase decisions (Y). The results indicate that both influencer credibility and social media content attractiveness have a positive and significant effect on purchase decisions for Saudare products via the Shopee platform. This suggests that a higher level of consumer trust in an influencer and more engaging content lead to increased consumer purchase decisions. Therefore, employing credible influencers and presenting attractive content are essential strategies for increasing online product sales   Keywords: Influencer Credibility, Content Attractiveness, Purchase Decision, Shopee